Hypertrophic Cardiomyopathy and Associated Coronary Artery Disease - Cokkinos, Dennis V. (1985)
Eighty-five consecutive patients with hypertrophic cardiomyopathy underwent hemodynamic evaluation and coronary arteriography to determine, in each case, the incidence and importance of coronary artery disease (CAD). Sixteen patients (19%) had >60% narrowing of the luminal diameter of one or more coronary arteries. Our findings revealed that patients with CAD were significantly older (mean, 64 years) than patients without CAD (mean, 42 years) and had a higher incidence of angina pectoris (81% versus 44%). Left ventricular end-diastolic pressures were lower in patients with CAD (mean, 17 mm Hg) than in those without CAD (mean, 23 mm Hg). The electrocardiographic findings were similar in both groups. There was no operative mortality in either group. In five patients with severe stenosis of the left anterior descending coronary artery (>90%), no collaterals to that artery were seen. In two, filling of the narrowed artery appeared slower than usual. Our study indicates that in patients older than 45 years of age with hypertrophic cardiomyopathy, the incidence of CAD is significantly higher, and warrants coronary arteriography prior to consideration for cardiac surgery. In this study, patients with hypertrophic cardiomyopathy and CAD who underwent corrective surgery for hypertrophic cardiomyopathy concomitantly with coronary artery bypass surgery have had low operative and long-term mortality with long-lasting symptomatic improvement.